Municipal Sukuk as Financing Model for Halal Tourism Development in West Sumatera, Indonesia - Mardian, Sepky; Armen, Rio Erismen (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2025)
Purpose: The study proposed a municipal sukuk model in strengthen halal tourism development in West Sumatera, Indonesia. After analyzing its opportunities and challenges within the context of limited local government financing.Design/methodology: The study employs a qualitative approach that combines literature review and field studies through interview as a technique of data collection. Interviews were conducted to the various stakeholders of halal tourism in West Sumatera. Six steps of the thematic analysis approach are employed to analyze the interview data. Discussion of findings was conducted by referencing the relevant research and other publications.Findings: The results show that stakeholders recognize municipal sukuk as a feasible instrument to finance halal tourism infrastructure. However, challenges remain, including the absence of specific local regulations, limited government assets, and insufficient technical capacity. Potential underlying assets include regional-owned hotels and tourist destinations, as well as tanah ulayat managed by nagari communities. Ijarah-based contracts, such as ijarah and ijarah maushufah fi al-zimmah, are identified as suitable structures for sukuk issuance.Practical Implication: The study provides policy insights for local governments and stakeholders in designing a regulatory and institutional framework for municipal sukuk, thereby enhancing sustainable halal tourism financing.Originality/Value: To the best of our knowledge, this is the first study to explore municipal sukuk for halal tourism development in Indonesia. It contributes to the literature on Islamic public finance by offering a novel model of sukuk issuance at the municipal level, extending the discourse on Islamic capital market instruments for regional economic development.